Gil de Biedma, Vallejo and Quevedo. Joaquín Sabina’s poetic influences - Soto Zaragoza, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The aim of this article is to analyze the poetic dimension of Joaquín Sabina’s lyrics and to approach their study from a strictly literary perspective. Due to the characteristics of his work, Sabina has been considered by several authorized voices a poet and a singer at a time. Just because, among other reasons, he is a great reader and a poetry lover. In this way, the influence of great names of Hispanic poetry can be traced in his lyrical work ─the sung one and the poetic one─. The echoes of Jaime Gil de Biedma, Francisco de Quevedo and César Vallejo stand out among a long list.